Physiological and biochemical changes in chickpea seedlings during acclimatization to low temperatures in the laboratory conditions (Experimental biology, 2018)
In this article represented the results of physiological and biochemical changes in 4 samples of chickpea seedlings at the stages of two variants’ cold acclimation under laboratory conditions.It was found that osmoprotectants: The free proline and sucrose increased as the lengthening and intensifying of the stress factors in all genotypes except for Malhotra variety. The informativeness of the biochemical parameters associated with overwintering was manifested during the period of temperature decrease from +13 to +2 оС. Thus, there were high positive correlations between accumulation of sucrose and the concentration of photosynthetic pigments, carotenoids (chlorophyll a, b, xanthophyll + carotenoids) in seedlings and overwintering level of chickpea in the field conditions (r = 0.98, 0.98, 0.91, respectively).At all stages of the 2nd variant in cold acclimation, the general activity of antioxidant enzymes (peroxidase, superoxide dismutase) was positively correlated with the level of sucrose and free proline in plants. When stress treatment was strengthened in plants, the relationship between peroxidase activity and the number of overwintered plants was revealed.
Keywords: chickpea, cold resistance, acclimatization, proline, sucrose, photosynthetic pigments, superoxide dismutase, peroxidase.